Attitudes of Chinese maternal and child health professionals toward termination of pregnancy for fetal anomaly: a cross-sectional survey - Wu, Ying; Liu, Yanlin; Wang, Xiaomin; Zhong, Yuqiong; Zhang, Xin; Luo, Dan; Liu, Xing (Frontiers in Public Health, 2023)
Objectives: This study explores the attitudes of Chinese maternal and child health professionals toward the termination of pregnancy for fetal anomaly (TOPFA) based on four case scenarios and further identifies the factors that influence their attitudes.This cross-sectional study, conducted from February 14-21, 2022, aimed to explore the attitudes of maternal and child health professionals toward TOPFA in Hunan Province. We targeted health service institutions across 14 prefecture-level cities and the autonomous prefecture. A questionnaire was made available online and shared via the instant communication platform, WeChat. Participants were recruited through the same platform and completed the survey online. Descriptive statistics were used to analyze the data, and binary logistic regression was performed to determine factors affecting the health professionals' attitudes toward TOPFA, expressed as the odds ratio (OR) and 95% confidence intervals (CI).The study found that 63.5% of health professionals approved of the birth of a fetus with cleft lip and palate, while 36.5% opposed it. Similarly, 39.7% approved of the birth of a fetus with phenylketonuria, while 60.3% opposed it. The percentages of those in favor of and against the birth of a fetus with precocious heart disease were 45.5% and 54.5%, respectively, and those for and against the birth of a fetus with missing fingers were 50.8% and 49.2%, respectively. The top three factors considered by health professionals when agreeing on TOPFA were "the impact of fetal disease on fetal function and growth," "the severity of fetal disease," and "the assessment of indications for fetal disease by professionals and related professional advice." The majority of health professionals (75-78%) preferred joint decision-making by parents regarding the right to decide TOPFA.Our study indicates that the attitudes of health professionals toward TOPFA can differ significantly depending on the specific birth defect under consideration. Notably, the majority of health professionals prioritized "the impact of fetal abnormalities on fetal function and development" when deciding their support for TOPFA, advocating for the decision to be a joint one between the parents.Additionally, factors such as religious beliefs, professional training, age, and job title appeared to influence these attitudes toward TOPFA.